Neurokinin-1 Receptor Antagonists Protect Mice from CD95- and Tumor Necrosis Factor-α-Mediated Apoptotic Liver Damage - Bang, Renate; Biburger, Markus; Neuhuber, Winfried; Tiegs, Gisa (Journal of Pharmacology and Experimental Therapeutics, 2004)
Previously, we have shown that primary afferent neurons are necessary for disease activity in immune-mediated liver injury in mice. These nerve fibers are detectable by substance P (SP) immunocytochemistry in the portal tract of rodent liver. Antagonists of the neurokinin-1 receptor (NK-1R), which is the prime receptor of SP, prevented liver damage by suppressing the synthesis of proinflammatory cytokines. Here, we investigated the influence of primary afferent nerve fibers, SP, and NK-1 receptor antagonists on hepatocyte apoptosis in vivo induced by administration of activating anti-CD95 monoclonal antibody (mAb) to mice. Depletion of primary afferent nerve fibers by neonatal capsaicin treatment prevented CD95-mediated activation of caspase-3, measured as enzymatic activity in liver homogenates or by demonstration of hepatocellular immunoreactivity for active caspase-3 in liver slices, and liver damage. This effect was reversed by administration of SP to anti-CD95 mAb-treated mice depleted from primary afferent neurons. The presence of the NK-1 R on mouse hepatocytes was demonstrated by immunocytochemistry and flow cytometry. Intraperitoneal pretreatment with the NK-1 receptor antagonists (2S,3S)-cis-2-(diphenylmethyl)-N-([2-methoxyphenyl]-methyl)-1-azabicyclo(2.2.2.) -octan-3-amine (CP-96,345) or (2S,3S)3-([3,5-bis(trifluoromethyl)phenyl]methoxy)-2-phenylpiperadine (L-733,060) dose dependently protected mice from CD95-mediated liver injury. Similar results were obtained when apoptotic liver damage was induced by administration of tumor necrosis factor-α to D-galactosamine-sensitized mice. In conclusion, SP, probably by binding to its receptor on hepatocytes, might aggravate apoptotic signals in these cells. Because NK-1 receptor antagonists not only suppress the proinflammatory cytokine response in the liver but also prevent liver cell apoptosis in vivo, they might be suitable drugs for treatment of immune-mediated liver disease.